Integrative analysis of transcriptome and miRNAome reveals molecular mechanisms regulating pericarp thickness in sweet corn during kernel development - Xiong, Caiyun; Pei, Hu; Zhang, Yahui; Ren, Wenchuang; Ma, Ziwei; Tang, Yunqi; Huang, Jun (Frontiers in Plant Science, 2022)
Pericarp thickness affects the edible quality of sweet corn (Zea mays L. saccharata Sturt.). Therefore, breeding varieties with a thin pericarp is important for sweet corn quality breeding. However, the molecular mechanisms underlying pericarp development remain largely unclear. We performed an integrative analysis of mRNA and miRNA sequencing to elucidate the genetic mechanism regulating pericarp thickness during kernel development (at 15 days, 19 days, and 23 days after pollination) of two sweet corn inbred lines with different pericarp thicknesses (M03, with a thinner pericarp and M08, with a thicker pericarp). A total of 2,443 and 1,409 differentially expressed genes (DEGs) were identified in M03 and M08, respectively. Our results indicate that phytohormone-mediated programmed cell death (PCD) may play a critical role in determining pericarp thickness in sweet corn. Auxin (AUX), gibberellin (GA), and brassinosteroid (BR) signal transduction may indirectly mediate PCD to regulate pericarp thickness in M03 (the thin pericarp variety). By contrast, abscisic acid (ABA), cytokinin (CK), and ethylene (ETH) signaling may be the key regulators of pericarp PCD in M08 (the thick pericarp variety). Furthermore, 110 differentially expressed microRNAs (DEMIs) and 478 differentially expressed target genes were identified. miRNA164-, miRNA167-, and miRNA156-mediated miRNA-mRNA pairs may participate in regulating pericarp thickness. The expression results of DEGs were validated by quantitative real-time PCR. These findings provide insights into the molecular mechanisms regulating pericarp thickness and propose the objective of breeding sweet corn varieties with a thin pericarp.